2007
DOI: 10.1097/hjh.0b013e32829c6a60
|View full text |Cite
|
Sign up to set email alerts
|

A new method for assessing 24-h blood pressure variability after excluding the contribution of nocturnal blood pressure fall

Abstract: Conventional 24-h SD of BP is markedly influenced by nocturnal BP fall. The weighted 24-h SD of BP removes the mathematical interference from night-time BP fall and correlates better with end-organ damage, therefore it may be considered as a simple index of 24-h BP variability superior to conventional 24-h SD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
178
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(186 citation statements)
references
References 17 publications
(37 reference statements)
2
178
1
5
Order By: Relevance
“…In dichotomous analyses, we defined systolic and diastolic nondipping as a night:day blood pressure ratio of Ն0.90. 1 As measures of short-term reading-to-reading blood pressure variability, we used the SD over 24 hours weighted for the time interval between consecutive readings (SD 24 ), the average of the daytime and nighttime SDs weighted for the duration of the daytime and nighttime interval (SD dn ), 25 and the average real variability weighted for the time interval between consecutive readings (average real variability in 24-hour ambulatory BP recordings; ARV 24 ). 4 The SD dn is the mean of day and night SD values corrected for the number of hours included in each of these 2 periods ( Figure 1A), according to the following formula 25 : SD dn ϭ[(day SDϫhours included in the daytime)ϩ(night SDϫhours included in the nighttime)]/(hours included in daytimeϩnighttime).…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…In dichotomous analyses, we defined systolic and diastolic nondipping as a night:day blood pressure ratio of Ն0.90. 1 As measures of short-term reading-to-reading blood pressure variability, we used the SD over 24 hours weighted for the time interval between consecutive readings (SD 24 ), the average of the daytime and nighttime SDs weighted for the duration of the daytime and nighttime interval (SD dn ), 25 and the average real variability weighted for the time interval between consecutive readings (average real variability in 24-hour ambulatory BP recordings; ARV 24 ). 4 The SD dn is the mean of day and night SD values corrected for the number of hours included in each of these 2 periods ( Figure 1A), according to the following formula 25 : SD dn ϭ[(day SDϫhours included in the daytime)ϩ(night SDϫhours included in the nighttime)]/(hours included in daytimeϩnighttime).…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…As mentioned above, there is no uniform standard of the normal SD or coefficient of variation of BP obtained from 24h ambulatory BP monitoring in different populations. Bilo et al [26] analyzed 24h ambulatory BP monitoring data on 3,863 Italian and Polish patients and found that the 24h SSD and 24h DSD were 13.8±3.7…”
Section: Discussionmentioning
confidence: 99%
“…Participants were regarded as hypertensive if their 24-h ABPM was X130 mm Hg and/or 80 mm Hg. 26 As a measure of short-term reading-to-reading BP variability, we used the average of the daytime and night time SDs weighted for the duration of the daytime and night time interval (wSD) as proposed by Bilo et al 17 and recommended by Hansen et al 4 …”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…of 24-h BP, average real variability index 16 and weighted 24-h BP s.d. 17 ) were being compared, regarding the strength of their association with target organ damage.…”
Section: Introductionmentioning
confidence: 99%